INNOVATIONS IN DESIGN AND CONSTRUCTION OF STATIONS MAINTENANCE OF AUTOMOBILES FOR PERSONAL USE (Municipal economy of cities. Series: «Economy science», 2013)
We analyze the development of the maintenance of cars for personal use in different historical periods. The concept and objectives of innovation in the design and construction of stations . Field maintenance of cars Ukraine should focus on the high growth rates of outputforeign technological level and innovation needed to improve the AI